Freshwater Decapod Diversity and Conservation in Central America and the Caribbean - Wehrtmann, Ingo S. (2016)
This chapter provides an overview of the species diversity and conservation status of the freshwater decapods in Central America and the Caribbean islands that date back to the late 1800s in both areas. The majority of the early studies were on taxonomy but our knowledge of freshwater decapod ecology (especially of freshwater shrimps from some Caribbean islands) has increased substantially over the last four decades. Currently, 86 species of freshwater decapods are known from Central America and the Caribbean. Here the decapod fauna comprises two families of primary freshwater crabs (Pseudothelphusidae and Trichodactylidae), three families of freshwater shrimps (Atyidae, Palaemonidae and Xiphocarididae), and one family of crayfish (Cambaridae). Several species have been introduced to this region for aquaculture and have now established wild populations. We also provide a list of Central American and Caribbean freshwater decapods that host parasites. To date, the conservation status of 43 % of all freshwater decapods in the region has been assessed using the IUCN Red List protocols; 5 % of these species are endangered or Critically Endangered, and two species (Cambarellus alvarezi and C. chihuahuae) are likely extinct. Cuba is the country with the most Vulnerable species (7 spp.), while Bermuda (2 spp.) and Barbados (1 sp.) have Critically Endangered species. The biodiversity of the freshwater decapod fauna of this region is still incompletely known despite recent efforts, and much more data need to be collected on species that are already known to be threatened with extinction, and on species that are too poorly known to assess. The high diversity of amphidromus caridean shrimps makes them especially vulnerable to threats from the modification of natural river systems such as the construction of dams for hydroelectric power or for water supply.